The Philosophical Meaning of Bamboo in Mabokuy Art and Ecoliteracy Purwaraja Community – Rajadesa - Ramdani, Dadan; Sudarto, Sudarto (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The bamboo woven craftsmen community in Purwaraja faces significant challenges amid global changes and a hedonistic lifestyle that prioritizes practicality over tradition. This research uses a qualitative ethnographic approach to explore the development and meaning of bamboo woven crafts in the Purwaraja community, focusing on societal value shifts and adaptive strategies to preserve local wisdom. Findings reveal the emergence of Mabokuy, a modern art form blending bamboo craft aesthetics with performing arts, reflecting the artist’s creativity and contemporary realities. Mabokuy arose from concerns about diminishing cultural awareness and loss of respect for nature. Bamboo symbolizes courage, natural beauty, strength, resilience, flexibility, loyalty, and respect—values deeply rooted in Sundanese arts and traditions where bamboo plays a vital cultural role. This art form not only entertains but also educates and promotes sustainable culture by fostering environmental awareness and cultural continuity. Mabokuy embodies ancestral tradition preservation, aiming to ensure its survival and relevance in the face of modernization. Ultimately, the art represents a sustainable cultural expression that reinforces the importance of environmental stewardship and community identity for future generations.